2023
DOI: 10.1002/bse.3596
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable development: The role of sustainability committees in achieving ESG targets

Aso Abdullah,
Sibel Yamak,
Anna Korzhenitskaya
et al.

Abstract: This study investigating the impact of sustainability committee characteristics (SCCs) on corporate sustainability performance (CSP) utilised environmental, social and governance (ESG) scoring. Based on secondary data obtained from Refinitiv, Fame and FTSE 150 databases, the sample consists of 112 non‐financial companies from 2010 to 2018, thus 926 firm‐year observations. The results reveal a positive and significant relationship between organisational factors including firm size, profitability and firm age ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 108 publications
0
0
0
Order By: Relevance
“…In addition, the results of this study differ from the findings conducted by (A. Abdullah et al, 2024), who concluded that no significant relationship was revealed between the presence of a Sustainability Committee and ESG scores. This statement pertains to greenwashing, a phenomenon where companies may falsely portray themselves as environmentally friendly or sustainable to deceive consumers, investors, or other stakeholders.…”
Section: Discussion Sustainability Committee and Esg Scorescontrasting
confidence: 99%
See 2 more Smart Citations
“…In addition, the results of this study differ from the findings conducted by (A. Abdullah et al, 2024), who concluded that no significant relationship was revealed between the presence of a Sustainability Committee and ESG scores. This statement pertains to greenwashing, a phenomenon where companies may falsely portray themselves as environmentally friendly or sustainable to deceive consumers, investors, or other stakeholders.…”
Section: Discussion Sustainability Committee and Esg Scorescontrasting
confidence: 99%
“…This correlation between sustainability committees and ESG Scores aligns with the principles of legitimacy theory, which posits that organizations strive to maintain their legitimacy by adhering to societal norms and expectations (A. Abdullah et al, 2024;Li et al, 2021). In the context of sustainability, companies with a dedicated sustainability committee demonstrate a proactive commitment to addressing environmental and social concerns, thereby enhancing their perceived legitimacy in the eyes of stakeholders.…”
Section: Discussion Sustainability Committee and Esg Scoressupporting
confidence: 61%
See 1 more Smart Citation